Program Baitul Arqam Bagi Pimpinan dan Dosen dalam Lingkup Universitas Muhammadiyah Enrekang Menggunakan Model CIPP - Bando, Ushwa Dwi Masrurah Arifin; Ismaya, Ismaya; Elihami, Elihami; Kamaruddin, Muh. Husain (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
In order to improve and foster the Leadership and Lecturers through Baitul Arqam activities oriented to the development of Islamic ideology and leadership in the scope of Muhammadiyah Enrekang University. Various problems that arise in this institution is not entirely Participants understand about Al-Islam and Muhammadiyahan which is implemented in daily life especially to the issue of Worship, Muamalah and Performance Improvement as well as social relations among Pimpanan and Lecturers. This event has been carried out for the first time since the campus changed its status from STKIP Muhammadiyah Enrekang to Muhammadiyah Enrekang University. This evaluation research is important to be conducted, because this activity is routinely carried out annually for the improvement and improvement of baitul Arqan activities next, this research uses cipp evaluation model, Medel CIPP Evaluation was created by Stufflebeam which focuses on four aspects, namely: Contex, Input, process and product, data collection and retrieval using several instruments, first interview, observation, and documentation. The research subjects that are used as data sources are Rector, Vice Rector I, Vice Rector II, Vice Rector III, Vice Rector IV Chairman of LPPK, Chairman of the Committee, Presenters and Lecturers at Muhammadiyah Enrekang University with a sample of 47 people. Evaluation category is divided into 5 sections, namely: Good, Good, Enough, Less, and less once. The evaluation results show: 1) Analysis of the needs and objectives and objectives of the program in the context component belongs to a very good category. 2) planning strategies that include materials, human resources, facilities and infrastructure, funds, and learning methods in the input component in baitul Arqam activities at Muhammadiyah Enrekang University are well-categorized. 3) in the process component carried out at Baitul Arqam activities for leaders and lecturers including good categories. 4) on the resulting product components fall into either category. From the evaluation, baitul arqam activities can be continued with various improvements in its implementation.